Fluorescence quantification of intracellular materials at the single-cell level by an integrated dual-well array microfluidic device. Issue 8 (18th March 2019) - Wang, Chenyu; Ren, Lufeng; Liu, Wenwen; Wei, Qingquan; Tan, Manqing; Yu, Yude
Abstract : We present an integrated microfluidic device for quantifying intracellular materials at the single-cell level. Abstract : We present an integrated microfluidic device for quantifying intracellular materials at the single-cell level. This device combines a dual-well structure and a microfluidic control system. The dual-well structure includes capture wells (20 μm in diameter) for trapping a single cell and reaction wells (200 μm in diameter) for confining reagents. The control system enables a programmable procedure for single-cell analysis. This device achieves highly efficient trapping of single cells, overcoming the Poisson distribution, while affording sufficient biochemical reagents for each isolated reactor. We successfully utilized the presented device to monitor the catalytic interaction between intracellular alkaline phosphatase enzyme and a fluorogenic substrate and to quantify the intracellular glucose concentration of a single K562 cell based on an external standard method. The results demonstrate the feasibility and convenience of our dual-well array microfluidic device as a practical single-cell research tool.